Multi-entrances security door system - Yasotha, Padmanathan (2012)
Over the years, several security measures have been employed to combat the menace of insecurity of lives and property. This is done by preventing unauthorised entrance into buildings through entrance doors using conventional and electronic locks or discrete access code. Thus, the main idea in this project is to design a database security system that allows only authorised user to enter the premises. There are two entry point with each using different technologies; RFID & keypad. Once the user’s identification is verified, the door is unlocked by using EDL (electronic door lock) and all the information such as user ID, date and time are stored in central office. The communication between the entrance points with central office by means of Zigbee wireless technology.